1998
DOI: 10.1002/(sici)1097-4636(199811)42:2<266::aid-jbm11>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

A complete characterization of Ca5(PO4)3OH sputter-deposited films by ion beam analysis: RBS and ERD

Abstract: RF magnetron sputter deposition was used to deposit thin calcium phosphate (hydroxyapatite) layers on titanium alloy substrate material. We determined the precise amount of calcium, phosphorus, oxygen, and hydrogen in these films by combining two ion-beam analysis techniques: Rutherford backscattering spectrometry (RBS) and elastic recoil detection (ERD). Variables were power level, partial oxygen pressure, or additional water vapor. Also examined was the influence of additional bias power to the substrates du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The Ca/P ratio of the coating layer is known to vary widely depending on the deposition procedures. 5,[12][13][14] The dissolution rate of the coating layer in the physiologic saline solution decreased with increasing Ca/P ratio until it reached the value for stoichiometric HA. However, when the Ca/P ratio exceeded 1.67, the dissolution rate increased again.…”
Section: Resultsmentioning
confidence: 99%
“…The Ca/P ratio of the coating layer is known to vary widely depending on the deposition procedures. 5,[12][13][14] The dissolution rate of the coating layer in the physiologic saline solution decreased with increasing Ca/P ratio until it reached the value for stoichiometric HA. However, when the Ca/P ratio exceeded 1.67, the dissolution rate increased again.…”
Section: Resultsmentioning
confidence: 99%
“…The calcium content of the target was determined to be 36% as compared to a theoretical value of 40% for stoichiometric hydroxyapatite. As discussed above, previous studies of RF magnetron sputtered hydroxyapatite have indicated that it is difficult to reproduce the exact stoichiometry of hydroxyapatite following deposition, , and therefore the quoted deficiency in calcium content of the target was deemed acceptable.…”
Section: Methodsmentioning
confidence: 99%
“…Further, the adherence of the coating to the substrate, the uniformity of the coating thickness, and the integrity of the structure are often poor . The plasma spraying technique has an additional drawback in the creation of a composite SF substrate; the coatings produced are at least a micrometer thick, far larger than the 100 nm or less required for SFG.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations